Planning an experiment to study the working cycle of a forklift - Sarkisov, Arsen (National Technical University "Kharkiv Polytechnic Institute", 2025)
The article examines the issue of durability of forklift components and the relationship between durability and operating conditions. The proposed parameters for studying a real forklift are presented.
Keywords: forklift; experiment; durability